Full Stack JavaScript Learn Backbone.js, Node.js, and MongoDB - Mardan, Azat (Apress, 2018)
Learn agile JavaScript web development using the latest cutting-edge front-end and back-end technologies including Node.js, MongoDB, Backbone.js, Parse.com, Heroku, and Microsoft Azure. Using a key project example of a message board app, you will learn the foundations of a typical web application: fetching data, displaying it, and submitting new data. Practical examples of the app build are provided with multiple technologies and all code examples are in full color. This book will save you many hours by providing a hand-picked and tested collection of quick start guides that will enable you to spend less time learning and more time building your own applications. Completely updated for this second edition, Full Stack JavaScript uses current versions of all technologies, including ES6/ES2015 and the latest versions of Node and npm. Prototype fast and ship code that matters!